Adaptive quality of service aware multi‐mobility anchor point registration in hierarchical mobile IPv6 wireless access networks. Issue 3 (1st September 2014) - Barkoosaraei, Ana Mirsayar; Aghvami, A. Hamid; Pangalos, Paul
Abstract : In hierarchical mobile IPv6 (HMIPv6), mobility anchor points (MAPs) are introduced to reduce the signalling cost by localising the signalling traffic of mobile nodes (MNs). However, the presence of MAPs introduces areas of bottleneck within the network. This study evaluates the impact of overlapped domains of consecutive MAPs in HMIPv6 access networks. In this novel network architecture, an MAP registration algorithm is also proposed to enable MNs to register with more than one MAP simultaneously. For each flow, the proposed algorithm determines a primary and a secondary MAP according to the quality of service (QoS) requirements of the traffic flow. Load balancing is also introduced to provide an even distribution of load among MAPs. In addition, an extended router advertisement is proposed to enable multiple MAP registration of MNs. The impact of the proposed algorithm in the new HMIPv6 network architectures is compared with a non‐QoS aware multi‐MAP registration algorithm in access network with no overlapped MAP domains. The simulation‐based comparison study illustrates a maximum of 71 and 74% improvements in total amount of rejected bandwidth and the mean satisfied flow requests in network, respectively.